Konsep Kerja Sosial Sebagai Alternatif Pidana Pokok Berperspektif Social Defence dan Budaya Moral dalam Upaya Penegakan Hukum Tindak Pidana Korupsi di Indonesia - Luna Dezeana Ticoalu; Relys Sandi Ariani; Herlin Sri Wahyuni (CV Rewang Rencang, 2021)
Corruption is still a major problem in Indonesia. Various efforts to eradicate corruption have been carried out, but in fact still less effective. This can be seen from several points of view. Firstly, the substance of the punishment stipulated in Corruption Laws has not given a deterrent effect to the perpetrators. Secondly, weaknesses in the legal structure of the functioning of authorized institutions. And thirdly, the culture of applying punishment is only juridical and does not emphasize the value of society (Shame Culture and Guilt Culture). Therefore, the author offers a solution to the problem, namely the Concept of Social Work as an Alternative criminal principle of Social Defence perspective in the Efforts to Enforce Corruption In Indonesia. This concept is the application of social work punishment into the principal criminal reviewed from the theory of Social Defence by integrating perpetrators into the community as an effort to instill the value of Shame Culture and Guilt Culture. The application of social work punishment into the principal criminal is reviewed from the theory of Social Defence and instills the value of Shame Culture and Guilt Culture by means of punishment cumulatively given with basic criminal punishment. This concept involves prosecutors, supervisory judges, and prisons in the implementation of social work. The research method used is juridical normative with statutory approach, conceptual approach, and comparison approach.